Knowledge and Practice about Sexually Transmitted Diseases among Childbearing Women at El-Fayoum City - Fayza Ahmed Ali Abdel-Baky; Entesar Fatouh Abdel Moniem; Fatma Abo El khair Farag (Indonesian Journal of Global Health Research, 2021)
Sexually Transmitted Diseases (STDs) still stand as one of the commonest health problems affecting women of reproductive age. The aim of this study was to assess the knowledge and practice about sexually transmitted diseases among childbearing women at El-Fayoum City. A descriptive study was used. A purposive sample composed of 100 women married and in childbearing age from the obstetric outpatient clinic at El- Fayoum University Hospital. Three tools were used (1)Structured Interviewing Questionnaire, (2) Knowledge assessment tool and (3) Practice assessment tool. Findings of the presenting study revealed that nearly one half of the studied women had low level of knowledge about STDs and nearly two thirds of them had unsatisfactory practice regarding STDs. According to the findings of the present study, one half of the studied women had low level of knowledge about STDs. Furthermore, nearly two thirds of them had unsatisfactory practice regarding STDs.